Silicon-nanocrystal-incorporated ternary hybrid solar cells. (August 2016) - Zhao, Shuangyi; Pi, Xiaodong; Mercier, Clément; Yuan, Zhongcheng; Sun, Baoquan; Yang, Deren
Abstract: Inorganic/organic ternary hybrid structures are emerging as promising candidates for the fabrication of novel solar cells. As one of the most important inorganic solar cell material, silicon (Si) is worth careful exploration during the preparation of the hybrid structures. Here we incorporate the nanoscale form of Si, Si nanocrystals (NCs), into the classical bulk-heterojunction organic solar cells based on poly (3-hexylthiophene) (P3HT) and [6, 6]-phenyl-C61-butyric acid methyl ester (PCBM). It is found that the solar cell efficiency may increase by ~ 40% when ~ 5% of PCBM in the original P3HT:PCBM blend is replaced with Si NCs. The efficiency enhancement is enabled by the improved short-wavelength absorption, optimized film structure and cascade energy-level alignment. Graphical abstract: Incorporation of silicon nanocrystals (Si NCs) into the classical bulk-heterojunction organic solar cells based on P3HT and PCBM leads to ternary hybrid solar cells. The solar cell efficiency may increase by ~40% when ~5% of PCBM in the original P3HT: PCBM blend is replaced with Si NCs. Highlights: Si nanocrystals (NCs) are added into the classical P3HT:PCBM organic solar cells. The power conversion efficiency may increase by ~40% when Si NCs are added. Si NCs improved solar cell absorption, structure and energy-level alignment.